Advance in Different Modes of Transcranial Magnetic Stimulation in Rehabilitation of Dysphagia after Stroke - Jiahui TAI; Junfa WU; Tingwei WANG; Yi WU (康复学报)
Dysphagia is one of the most common functional disorders after stroke, with an incidence of up to 30%-50%, resulting in malnutrition and aspiration pneumonia, which could be life-threatening. The pathogenic mechanism of dysphagia after stroke involves multiple brain functional areas and neural networks. It is generally believed that dysphagia after stroke is related to the lesions of cerebral cortex, subcortical structures and brainstem swallowing center. There are significant differences in the mechanism and clinical manifestations of dysphagia caused by different lesion sites. Understanding the mechanism is conducive to the development of more targeted and individualized rehabilitation therapy in clinical practice, which has an important impact on the prognosis of patients. Except for the traditional swallowing treatment programs commonly used, such as swallowing motion-sensory training, peripheral neuromuscular electrical stimulation, acupuncture, postural training, and dietary adjustment, people have become more and more interested in central nervous regulation in the treatment of swallowing dysfunction. Transcranial Magnetic Stimulation(TMS), as a non-invasive neuroregulation technique, achieves the purpose of neuroregulation by regulating the excitability of the cerebral cortex. With the development of research, different pulse stimulation patterns have been developed and experimentally applied in the treatment of post-stroke dysphagia. Repetitive transcranial magnetic stimulation(rTMS)is a repeated, continuous and constant intensity stimulation of selected brain regions. Theta burst stimulation(TBS)is based on rTMS with the addition of cluster rhythmic stimulation, which has lower stimulus intensity and shorter stimulus duration. Paired associative stimulation(PAS)combines central TMS with peripheral electrical stimulation at certain intervals to activate brain networks in pairs. Each mode of treatment has its own characteristics. This article reviews the application of different stimulation modes in healthy people and patients with dysphagia after stroke, analyzes the current research progress and limitations in this field, and provides a new idea for the clinical research and treatment of deglutition disorder after stroke from three points.